Effects of Concentration, Temperature and Solvent Composition on the Partial Molar Volumes of Sodium Polystyrenesulphonate in Methanol -Water Solvent Media - Bhattarai, Ajaya; Das, Bijan (Journal of Nepal Chemical Society, 2009)
Precise measurements on the density of sodium polystyrenesulphonate solutions in methanol-water mixed solvent media containing 8, 16, and 25 weight per cent of methanol at 308.15, 318.15, and 323.15 K are reported. The degree of substitution of sodium polystyrenesulphonate used is 1, and the concentrations are varied from 1×10-2 to 3.8 ×10-2 monomol.l-2. The results showed a slight increase on (V0) were determined. the partial molar volumes with increasing polyelectrolyte concentration. The partial molar volumes of the polyelectrolyte at infinite dilution, (effects of the temperature and solvent composition on the partial molar volumes are also investigated. Keywords: Sodium polystyrenesulphonate, polyion, partial molar volume. DOI: 10.3126/jncs.v23i0.2100 Journal of Nepal Chemical Society, Vol. 23, 2008/2009 Page: 82-88